The Causality between Diabetes and Venous Thromboembolism: A Bidirectional Two-Sample Mendelian Randomization Study - Hu, Song; Tan, Jiang-Shan; Hu, Meng-Jin; Guo, Ting-Ting; Chen, Liyuan; Hua, Lu; Cao, Jian (Thrombosis and Haemostasis, 2023)
Background Diabetes was considered as a risk factor for venous thromboembolism (VTE), but conflicting findings have been reported from observational studies. This study aimed at investigating the causal associations of type 1 and type 2 diabetes with VTE, including deep vein thrombosis (DVT) and pulmonary embolism (PE).Methods We designed a bidirectional two-sample Mendelian randomization (MR) analysis by using summary-level data from large genome-wide association studies performed in European individuals. Inverse variance weighting with multiplicative random effect method was used to obtain the primary causal estimates, and weighted median, weighted mode, and MR egger regression were replenished as sensitivity analyses to test the robustness of the results.Results We found no significant causal effects of type 1 diabetes on VTE (odds ratio [OR]: 0.98, 95% confidence interval [CI]: 0.96–1.00, p = 0.043), DVT (OR: 0.98, 95% CI: 0.95–1.00, p = 0.102), and PE (OR: 0.98, 95% CI: 0.96–1.01, p = 0.160). Similarly, no significant associations of type 2 diabetes with VTE (OR: 0.97, 95% CI: 0.91–1.03, p = 0.291), DVT (OR: 0.96, 95% CI: 0.89–1.03, p = 0.255), and PE (OR: 0.97, 95% CI: 0.90–1.04, p = 0.358) were also observed. Results from multivariable MR analysis were consistent with the findings in univariable analysis. In the other direction, the results showed no significant causal effects of VTE on type 1 and type 2 diabetes.Conclusion This MR analysis demonstrated no significant causal associations of type 1 and type 2 diabetes with VTE in both directions, in conflict with previous observational studies reporting positive association, which provided clues for understanding the underlying pathogenesis of diabetes and VTE.
Keywords: diabetes; venous thromboembolism; deep vein thrombosis; pulmonary embolism; Mendelian randomization